Process development and optimization for biocatalytic production of irones from iris root - Mohlala, Ronny Mogege (My University, 2016)
Irones are the pleasantly smelling terpenoids of orris oil used in the fragrance industry that are extracted from the rhizomes of Iris species through a lengthy process. Unfortunately syntheses of irones using chemical methods or Iris rhizome-derived sources have been reported to be long, unsafe and low yielding. These inefficient methods have therefore resulted in a high cost of the orris absolute (an alcohol extract of orris butter) which costs between 40 000 and 70 000 Euros/kg. A promising enzymatic process for irones production with good conversion of the precursors has been reported. However, the processing of the irone source into iridals (irone precursors) requires high temperatures and as a result the safety as well as energy input of the method is affected. Moreover, the prior solvent extraction was reported to affect the quality of the product. The present research aimed to develop a rapid and effective enzymatic process for the production of α- and γ-irones at 2L scale-up, as well as obtaining the final product in the form of orris butter. During the current studies a method for analysis of the irones samples was developed, and subsequently different solvents were investigated to identify the best sampling method. Thereafter different oxidoreductases were screened to identify the best enzyme source for maximum production of irones. Optimization of temperature, loading of lipoxidase, orris root, oleic acid, and dioxane, the ratio of minerals to irone concentration, incubation period and use of anti-fungal agents were investigated for maximum irones production. Furthermore, different methods to concentrate the irones and to produce the final orris butter product were evaluated. Lastly, testing the effect of purifying the enzyme on the production of irones was investigated. At laboratory scale the optimum reaction conditions were found to consist of incubating 5 g of fresh homogenised orris root with 20 mL crude soybean lipoxidase (prepared as 1 g soybean flour in 25 mL of 0.01 M borate buffer pH 9.2), with 50 mg manganese chloride and 25 mg ferrous sulphate, 1 mL dioxane and 0.25 mL oleic acid, for 5 days at 37°C in a rotatory shaker incubator. The laboratory scale product could be recovered by using a mixture of equal proportions of acetone and-DMSO for sampling under stringent sterile conditions. At the 700 mL and 2L scale it was determined that with improved agitation and oxygenation of the reaction mixture and subjecting the maturated suspension to Likens-Nickerson distillation resulted in the required orris butter profile. It was further found that purification of the enzyme reduced its ability to efficiently convert the precursors in fresh orris root into irones. Alpha (α-) and gamma (γ-) irones) of the same retention times (3.79 and 3.82) and mass (207 Da) as the α-irone commercial sample were produced at yields around 696 mg irone/kg dry orris root compared with 530 mg irone/kg dry orris root seen with traditionally processed rhizome. The current research is the first to use crude soybean lipoxidase to oxidize macerated fresh orris root into irones, and the first to identify the importance of minerals in the bioconversion.
Dissertation submitted for the qualification Master of Science in Chemistry (full time) University of Witwatersrand November 2015
Keywords: Irises (Plants); Roots (Botany)